Whistleblowing : law and practice. - Lewis, Jeremy, 1968-; Bowers, John, 1956-; Fodder, Martin; Mitchell, Jack (Oxford : Oxford University Press, 2022)
This title offers a detailed survey of the law relating to public interest disclosure, covering protection for whistleblowers both under and outside of the Public Interest Disclosure Act 1998.
Previous edition: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 23, 2022).
Keywords: Whistle blowing -- Law and legislation -- Great Britain; Disclosure of information -- Law and legislation -- Great Britain; Law; Laws of specific jurisdictions & specific areas of law